First (p,n) reaction measurement in inverse kinematics with SECAR - Tsintari Pelagia; Berg Georg; Blackmon Jeff; Chipps Kelly; Couder Manoel; Deibel Catherine; Dimitrakopoulos Nikolaos; Garg Ruchi; Greife Uwe; Hermansen Kirby; Hood Ashley; Jain Rahul; et al. (EPJ Web of Conferences, 2023)
Nucleosynthesis in the νp-process occurs in regions of slightly proton-rich nuclei in the neutrino-driven wind of core-collapse supernovae. The process proceeds via a sequence of (p,γ) and (n,p) reactions, and depending on the conditions, may produce elements between Ni and Sn. Recent studies show that a few key (n,p) reactions regulate the efficiency of the neutrino-p process (νp-process). We performed a study of one of such (n,p) reactions via the measurement of the reverse (p,n) in inverse kinematics with SECAR at NSCL/FRIB.Such proton-induced reaction measurements are particularly challenging, as the recoils and the unreacted projectiles have nearly identical masses. An appropriate separation level can be achieved with SECAR, and along with the incoincidence detection of neutrons these measurements become attainable. The preparation of the SECAR system for accommodating its first (p,n) reaction measurement, including the development of alternative ion beam optics, and the setup of the in-coincidence neutron detection, along with discussion on preliminary results from the p(58Fe,n)58Co reaction measurement are presented and discussed.